(untitled) (Dialogos, 2018)
Resumo. O presente artigo trata da relação entre Educação e Patrimônio, com o fito de apresentar a importância do desenvolvimento da educação patrimonial no contexto escolar. Tratamos dos seguintes tópicos: 1) aspectos conceituais e legais relativos ao patrimônio; 2) o papel da educação patrimonial na formação da cidadania e seu lugar pedagógico no ensino; 3) apreciação crítica de 4 títulos referentes ao assunto, publicados no ano de 2004 no estado do Rio Grande do Sul/Brasil. Abstract. The present article goes on the relation between Education and Cultural Heritage, aiming to present the importance of the development of Heritage education in the scholar context. We deal with the following topics: 1) conceptual and legal aspects concerning the cultural Heritage; 2) the role of the Heritage education in the building of the citizenship and its pedagogical place in the scholar instruction; 3) critical appreciation of 4 titles concerning the subject, issued in the year 2004, in the state of Rio Grande do Sul.